Methods Of Improving Technological Quality In Cleaning Grain Mixtures From Waste Based On Gost Requirements - Sayidaxmedov Ravshan Rajabovich; Xo’jjiyev Ma’murjon Yangiboyevich (Zien Journals, 2024)
In this article, the main feature of the technological process in the grain cleaning department is the effective process of dry and wet cleaning of the grain surface. Taking into account the structural and mechanical properties of wheat varieties grown in Uzbekistan, and soil and climatic conditions, the process of cleaning the grain surface consists of several stages. In addition to reducing their ash content during dry and wet processing of the upper layers of grains, information is provided on the technology for cleaning grains from various microorganisms.
Keywords: cocoon; gluten; grinding